Kolaborasi Membangun Karakter Anak Berkebutuhan Khusus Sekolah dan Orang Tua di SLBN Sambirejo - Suharni Suharni; Asroful Kadafi; Beny Dwi Pratama (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Character is the result of good habituation that must be instilled in every child, this is no exception for every child. Every parent will not want their child to have limitations or special needs. The treatment of all children should certainly not be discriminated against, and it is strongly recommended not to discriminate. However, the real conditions in the field are still problematic. The development of students' potential is certainly not only based on academic ability. One of the no less important is to build the character of the child. The purpose of this community service activity is to provide understanding to people in their role to improve the character of discipline and responsibility, the role of teachers in educational units in building discipline and responsibility and how parental collaboration will be used as an idea to improve the characteristics of character potential that wants to be developed in each child or student through parental empowerment activities as a form of implementation  independent curriculum. Furthermore, this service activity hopes to have a significant impact on developing children's character through collaborative activities with parents and schools with various more creative and innovative activities in giving independence to children.